2018
DOI: 10.1038/s41591-018-0011-0
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressive effects of targeting ELK-1 signal transduction

Abstract: Depression, a devastating psychiatric disorder, is a leading cause of disability worldwide. Current antidepressants address specific symptoms of the disease, but there is vast room for improvement . In this respect, new compounds that act beyond classical antidepressants to target signal transduction pathways governing synaptic plasticity and cellular resilience are highly warranted. The extracellular signal-regulated kinase (ERK) pathway is implicated in mood regulation, but its pleiotropic functions and lack… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
30
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 58 publications
2
30
1
1
Order By: Relevance
“…Our results above suggest that GPR56 may be involved in mechanisms associated with antidepressant response that are common to different classes of antidepressants, but interestingly, not involved in mechanisms of placebo response. To further examine the potential function and regulation of Gpr56 in depression and antidepressant response, we conducted studies in animals, using the unpredictable chronic mild stress (UCMS) paradigm, a well validated murine model of depression 5 , followed by treatment with fluoxetine, a standard SSRI, to model antidepressant effects ( Fig. 2a).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our results above suggest that GPR56 may be involved in mechanisms associated with antidepressant response that are common to different classes of antidepressants, but interestingly, not involved in mechanisms of placebo response. To further examine the potential function and regulation of Gpr56 in depression and antidepressant response, we conducted studies in animals, using the unpredictable chronic mild stress (UCMS) paradigm, a well validated murine model of depression 5 , followed by treatment with fluoxetine, a standard SSRI, to model antidepressant effects ( Fig. 2a).…”
Section: Resultsmentioning
confidence: 99%
“…In this model, stress-exposure leads to depressive-like behaviors (displayed as increased anhedonia and/ or resignation) that can be alleviated by subsequent administration of an antidepressant. We have previously adapted this model to distinguish between responder and non-responder mice 5 . Here, chronic stress-induced depressive-like behaviors were effectively reversed in 60% (responders) of the fluoxetine-treated mice.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Dr. Tzavara's group at Sorbonne University in France reported that ELK-1, a transcription factor (TF) and a major downstream target of the ERK signaling pathway, is upregulated both in depressive suicides and in animal models of depression induced by unpredictable chronic mild stress (UCMS) and social defeat (Apazoglou et al, 2018 ). They also found that patients who responded to antidepressant treatment had significantly lower blood levels of ELK-1 than nonresponders.…”
mentioning
confidence: 99%
“…Furthermore, the authors showed that virally overexpressing ELK-1 in the dentate gyrus (DG) of mice induced depression-like behaviors. Injection of blood–brain barrier-permeable TAT-DEF-ELK-1 (TDE) peptide, which disrupts ERK-mediated ELK-1 phosphorylation (activation) in the DG, improved behavioral signs in the depression models and in mice overexpressing ELK-1, without affecting basal levels of locomotion and memory (Lavaur et al, 2007 ; Apazoglou et al, 2018 ). The authors conclude that the induced expression of genes by enhanced ELK-1 activity may be critical for depressive symptoms.…”
mentioning
confidence: 99%